Atorvastatin-Induced Hepatotoxicity, Increased by Clopidogrel Stress on CYP450 Enzyme: Understanding the Mechanism through a Case - Sahithi Thotakura, Ajit Singh, Kanav Khera, Sheetal Chauhan, Tom Devasia (Journal of Applied Pharmaceutical Science, 2018)
Statins are widely used drugs for both primary and secondary prevention of various cardiovascular disorders. Cases have been reported on statin-induced hepatitis where the elevation of liver enzymes leads to hepatotoxicity. Here we present a patient with atorvastatin-induced hepatotoxicity and the mechanism accelerated by clopidogrel use. The drugs which are metabolized by CYP450 can increase the risk of hepatitis. CYP4503A4 enzyme metabolizes both atorvastatin and clopidogrel. In this case, clopidogrel has shown the synergistic effect which is responsible for the significant liver injury.
Keywords: Hepatotoxicity, Coronary artery disease, Alanine aminotransferase, Aspartate aminotransferase, Medication non-compliance, RUCAM Score.